Real Time Comparison between PID and Fuzzy Logic Controller for DC Motor Speed Control - Ridzuan, Akmal; Abdul Rahman, Hisyam (Evolution in Electrical and Electronic Engineering, 2024)
The diversity in DC motor application in robotic, heavy manufacturing and transportation have caused the usage of the controller in speed control mechanism become a main priority. PID controller is a common controller used in the industry due to its esy and straightforward design. However, the PID controller face challenges when the plant model contains the nonlinear characteristics. To overcome this situation, Fuzzy Logic controller is used as the controller as it can make decision based on the uncertain and vague inputs. In this study, the PID and Fuzzy Logic is applied and analyzed to decide the controller with better output response. The overshoot, undershoot, transient time and settling time are the indicator used to compare the controller output response. The hardware DC model is integrated with the Simulink DC motor model by STM32F411RE microcontroller. System identification is used to determine the plant model transfer function for the PID controller design process. The Fuzzy Logic controller is designed in MATLAB Fuzzy Logic Toolbox. 25 fuzzy rules are derived from five memberships function that are applied in the Fuzzy Logic controller design for the inputs and output. The result implies that Fuzzy Logic controller have a better response than the PID controller. This is shown by the lower overshoot of 0.7746% compared to PID overshoot of 3.4619%. The time taken for transient and settling time is shorter by using Fuzzy Logic controller by 1.1805s compared to PID controller transient and settling time of 1.2236. The output response waveform of both controllers are being observed and compared in this paper.